scPower accelerates and optimizes the design of multi-sample single cell transcriptomic studies - Katharina T. Schmid (Nature Portfolio, 2021)
scRNASeq data is revolutionizing our understanding of biological systems, but is still expensive to generate. Here, the authors present a statistical framework that facilitates informed multi-sample experimental design to reduce unnecessary costs and maximize the utility of the generated data.